1972
DOI: 10.1111/j.1399-0004.1972.tb01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the XYY karyotype in one of two brothers with congenital adrenal hyperplasia

Abstract: One of two brothers with the virilizing adrenogenital syndrome manifested slow psychomotor development and was initially diagnosed as having “infantile autism”. He developed an osteogenic sarcoma, and skin, lymphocytes and cultured tumor cells showed a 47, XYY karyotype. The younger brother shows normal behavior and has a 46, XY chromosome constitution. Both children showed the same hormonal response to steroid suppression therapy, but the XYY boy continued in an abnormal growth pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 14 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…No study has directly examined whether autism is more common in girls with congenital adrenal hyperplasia, although there is a case report of a boy born with congenital adrenal hyperplasia and an XYY chromosomal karyotype who was described as having autism. 133 A recent study, however, has found that girls with congenital adrenal hyperplasia have a higher Autism-Spectrum Quotient score than their unaffected sisters (Knickmeyer RC et al, submitted for publication). In addition, girls with congenital adrenal hyperplasia score lower than control girls on measures assessing empathy, intimacy, and the need for close social relationships.…”
Section: Disorders Of Sexual Developmentmentioning
confidence: 99%
“…No study has directly examined whether autism is more common in girls with congenital adrenal hyperplasia, although there is a case report of a boy born with congenital adrenal hyperplasia and an XYY chromosomal karyotype who was described as having autism. 133 A recent study, however, has found that girls with congenital adrenal hyperplasia have a higher Autism-Spectrum Quotient score than their unaffected sisters (Knickmeyer RC et al, submitted for publication). In addition, girls with congenital adrenal hyperplasia score lower than control girls on measures assessing empathy, intimacy, and the need for close social relationships.…”
Section: Disorders Of Sexual Developmentmentioning
confidence: 99%